Analysis of Gap in Service Quality through SERVQUAL:A Case of Deposit Service Provided by a Bank in Bangladesh - Shil, Nikhil Chandra; Das, Bhagaban (Indian Journal of Marketing, 2009)
To remain profitable and strong in the market, retaining current customers and attracting potential customers has no alternative. This can only be done if the customers are kept satisfied and if the gap between expectation and perception of services are minimal. Thus, the analysis of gap on a regular basis and following the improvement, if any, is very important. In this paper, such analysis of gap is initiated on deposit service of a multinational bank operating in Bangladesh. For this gap analysis, SERVQUAL is used as a tool with five original dimensions and twenty two statements. A questionnaire survey is administered to calculate the gap score using SERVQUAL scale and thrust areas have been identified on the basis of the gap score where management should give more attention.